Renal implant using minimally invasive surgery: Experience in a center - Medeiros, Vitória Nunes (2016)
Introduction: Minimally invasive kidney transplantation approaches have recently been described, and more research is needed on this subject. There is scarce information on the perioperative management in those patients. Therefore, in the present study, we describe the experience in a transplant center with minimal incision techniques in renal transplant surgeries. In addition, we describe the main results of the procedures. Purpose: To describe the experience in a tertiary center, which performed renal transplants with 20 minimally invasive incisions, reporting their complications and comparing data in the literature. Methods: A retrospective cohort study including 20 kidney transplant recipients from living and deceased donors in a single center, who underwent minimally invasive surgery between July 2010 and May 2011. Minimally invasive surgery was defined as that with incision size from 5 to 9 centimeters. We assessed surgical complications, duration of hospitalization, delayed graft function (DGF), and renal function at 10 weeks. Results: Of the 20 patients studied, 12 were male and 8 were female. The mean age was 43 years. 17 patients were transplanted with kidney from deceased donors. The mean HLA mismatch was 4.3 and no patient had a positive reaction in PRA. The cold ischemia time was in average 15.7 hours, ranging from 1 to 26 hours. The size of the incisions ranged from 5.5 to 9 cm, with mean size of 7.6cm. There was only one complication requiring re-approaching (perirenal hematoma). The mean hospital stay was 19.2 days. 40% of patients had DGF, and there was no graft loss. The mean creatinine after 10 weeks was 1.5 mg/dl. Conclusions: Kidney transplantation with minimally invasive incision proved to be a safe strategy with a low percentage of complications.